Note on Capillary Rise in Elliptic and Semielliptic Tubes - Rajai S. Alassar (Journal of Applied Mathematics)
In this note, the dimensions of elliptic and semielliptic tubes in which the capillary rise starts oscillating about its Jurin’s height are determined. Comparisons with the capillary rise in the classical circular and in semicircular tubes are made.